Saturday

April 19, 2014

April 19, 2014

Posted by **Peter** on Monday, October 3, 2011 at 12:48am.

x = 3y + 4

6y = 2x - 6

- Algebra 2 -
**PsyDAG**, Monday, October 3, 2011 at 1:42amAdd six to both sides of the first equation.

2x = 6y + 6

x = 3y + 4

Multiply second equation by two.

2x = 6y + 8

If you subtract the revised second equation from the first, what does it give you?

**Related Questions**

algebra - solve the system of equations by graphing. Then classify the system as...

Math 116 - Consider the following system of equations. y=2x-2 y-2x=9 What can ...

Math 1 - Consider the following system of equations. y = 4x - 4 y - 4x = 3 What...

Algebra - Suppose a linear system of equations has 2012 equations and 2013 ...

algebra - Can someone please help. When you solve a system of equations by the ...

algebra - When you solve a system of equations by the substitution method, how ...

algebra - Can someone help me figure this out please? when you solve a system of...

math - Consider the following system of equations. Y = 3x – 7 Y - 3x = 5 a) The ...

algebra - Can someone please help. Explain how you can determine from the graph ...

math - Determine whether the ordered pair is a solution of the inequality (5, 12...